16. INTRACYTOPLASMIC SPERM INJECTION IS NOT NECESSARY AS A PREVENTIVE MEASURE AGAINST PATERNAL CELL CONTAMINATION IN PREIMPLANTATION GENETIC TESTING. (August 2019) - Lynch, C.; Cater, E.; Charitou, M.; Forbes, H.; Griffin, D.; Gordon, T.
Abstract : Introduction: Conflicting information exists as to which method of insemination to use for PGT patients. Recommendations from some professional bodies advise the use of intracytoplasmic sperm injection (ICSI) for insemination for all amplification based testing to reduce the risk of paternal contamination from extraneous sperm bound to the zona pellucida, or non decondensed sperm within blastomeres. The vast majority of PGT is now performed via amplification based techniques, beginning with whole genome amplification of the submitted samples. Therefore, it is important to examine the need for this additional and expensive intervention for such a large number of patients that could undergo and achieve fertilisation via conventional in vitro fertilisation (IVF). Materials and Methods: Semen samples were obtained from 5 male patients consenting to research. The semen sample was prepared as per the IVF laboratory standard operating procedure for sperm preparation for IVF/ICSI insemination. From each sample 1, 2, 4, 8 and 10 sperm were collected in PCR tubes and submitted to the genetic testing laboratory as blinded research samples. The tubed sperm samples underwent whole genome amplification via SurePlex, and DNA amplification was assessed via gel electrophoresis, in line with PGT sample processing. Results: All results were as expected for internal positive and negative controls. However, none of the 25 tubed sperm samples submitted showed evidence of DNA amplification. Conclusions: Sperm DNA failed to amplify under the conditions used to process polar body, blastomere and trophectoderm samples in PGT. DNA can be amplified from individual sperm, but requires additional sperm DNA decondensation steps. Therefore, paternal cell contamination resulting from using IVF as the insemination method is a negligible risk and ICSI, in the absence of male factor infertility, is an unnecessary intervention for PGT patients.